2021
DOI: 10.1021/acs.chemrev.1c00438
|View full text |Cite
|
Sign up to set email alerts
|

Sonoprocessing: From Concepts to Large-Scale Reactors

Abstract: Intensification of ultrasonic processes for diversified applications, including environmental remediation, extractions, food processes, and synthesis of materials, has received attention from the scientific community and industry. The mechanistic pathways involved in intensification of ultrasonic processes that include the ultrasonic generation of cavitation bubbles, radical formation upon their collapse, and the possibility of fine-tuning operating parameters for specific applications are all well documented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 341 publications
0
65
0
Order By: Relevance
“…The effective calorimetric power ( ) [39] , [40] , [41] was used to quantify the energy transfer efficiency of the sonochemical reactor in our work. 3 L of black concentrated sulfuric acid (equivalent to a sulfuric acid mass of 5.52 kg) was directly sonicated with an ultrasonic power density of 200 W·L −1 (equivalent to an ultrasonic power of 600 W) without any cooling for 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…The effective calorimetric power ( ) [39] , [40] , [41] was used to quantify the energy transfer efficiency of the sonochemical reactor in our work. 3 L of black concentrated sulfuric acid (equivalent to a sulfuric acid mass of 5.52 kg) was directly sonicated with an ultrasonic power density of 200 W·L −1 (equivalent to an ultrasonic power of 600 W) without any cooling for 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…Achieving high levels of cavitation power through multi-transducer vessels, particularly where geometrical focusing allows lower individual transducer operating levels, produces robust and repeatable processing capabilities, and can also generate cavitation over large liquid volumes. For industrial manufacturing, the sonication process needs to be applied and monitored consistently to large volume batches to enable upscaling of production, and this can be achieved using multi-transducer sonication cells [19] , [26] , [39] of the type considered here, designed and configured for eventually achieving flow-based processing. Having control over the sonication dose by removing potential sources of set-up uncertainty means a higher reproducibility and consistency between processed batches can be attained.…”
Section: Discussionmentioning
confidence: 99%
“…The main limit of ultrasound-assisted synthetic approaches lies in their scalability. Most studies report batch syntheses of small amounts of photocatalysts and sonoprocessing is notoriously dependent on reactor geometry [8]. In this respect, Zhu et al [24] reported a continuous flow reactor (Fig.…”
Section: Ultrasound-assisted Synthesis Of Photocatalystsmentioning
confidence: 99%
“…1a). However, these phenomena are primarily dependent on experimental parameters like ultrasound frequency and power, medium properties, operating conditions, and reactor geometry [8]. For instance, ultrasound waves with low frequency (20−80 kHz) cause mainly physical effects, whereas chemical effects dominate at high frequencies (150−2000 kHz).…”
Section: Introductionmentioning
confidence: 99%